2019
DOI: 10.3390/nu11061313
|View full text |Cite
|
Sign up to set email alerts
|

How Patients with IBS Use Low FODMAP Dietary Information Provided by General Practitioners and Gastroenterologists: A Qualitative Study

Abstract: There is a lack of dietitians trained to deliver the low fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) diet (LFD) for irritable bowel syndrome (IBS). Many patients receive nutritional information from general practitioners (GPs) or gastroenterologists (GEs). Since the LFD is dietitian-led, the aim of this research was to qualitatively explore the effects of GP- and GE-delivered LFD information, in IBS self-management. Semi-structured interviews were conducted in a purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…Meanwhile, a qualitative interview study of patients who had received low-FODMAP dietary education from a family physician or gastroenterologist, but not a dietitian, reported the advice to be too simplistic, with little personalization and requiring substantial interpretation. 116 Indeed, in a retrospective analysis of dietary change in patients prescribed a low-FODMAP diet, education by a dietitian achieved the goals of the dietary strategy to a significantly greater extent than nondietitian education in which poor implementation led to incomplete FODMAP restriction and unsuccessful or absent reintroduction and personalization. 117 These are likely to reduce the chance of achieving optimal clinical benefit and patient self-empowerment.…”
Section: Implementation Of Low-fodmap Dietmentioning
confidence: 99%
“…Meanwhile, a qualitative interview study of patients who had received low-FODMAP dietary education from a family physician or gastroenterologist, but not a dietitian, reported the advice to be too simplistic, with little personalization and requiring substantial interpretation. 116 Indeed, in a retrospective analysis of dietary change in patients prescribed a low-FODMAP diet, education by a dietitian achieved the goals of the dietary strategy to a significantly greater extent than nondietitian education in which poor implementation led to incomplete FODMAP restriction and unsuccessful or absent reintroduction and personalization. 117 These are likely to reduce the chance of achieving optimal clinical benefit and patient self-empowerment.…”
Section: Implementation Of Low-fodmap Dietmentioning
confidence: 99%
“…A recent study by Trott et al showed how general practitioners in the UK, who are often the first contact of the IBS patient with the health system, do not have the knowledge to propose the LFD without the risk of encountering several nutritional risks, such as causing a micronutrient deficiency micronutrients or an unnecessary weight loss [69]. Educational groups could be timesaving for health professionals and could be useful for improving the patients' knowledge of LFDs.…”
Section: Complex and Difficult To Teach And To Learnmentioning
confidence: 99%
“…In addition to the need for long-term data, future studies should assess the ability of patients to be compliant with the low FODMAP diet. It is thought that dietitian guidance is key to the success of the diet [38], but further data is needed to understand dietary compliance, nutritional adequacy and effects on the microbiota profile both in the short- and long-term depending on mode of education (i.e., dietitian taught, physician taught or self-implemented).…”
Section: Sensitivities (Non-allergic)mentioning
confidence: 99%